Peer victimization: Intimidation and victmization in Chilean students - López, Verónica (2009)
This paper presents the results of a study about peer intimidation and victimization with 1167 school students from 6th, 7th, and 8th grade from the Valparaiso Region of Valparaíso, Chile. The instrument used was the Insebull Battery (Avilés & Elices, 2007). Results show that approximately 9% of students have been victim of peer victimization many times or almost every day during the school year. Psychological victimization was more frequent thanphysical aggression, particularly through virtual communication such as cell-phone messages and e-mails. Participants tend to be groups of male students. Although male students participate more in physical aggression, they also receive more physical and psychological aggression. The most frequent places were inside the classroom and the school yard, when the teacher is not present. Most students inform not knowing, or vaguely knowing, thereasons underlying these aggressions, and do not do anything to deal with them. These results coincide with international studies and allow a better understanding of the characteristics of peer victimization in specific educational contexts within the Chilean school system.